(untitled) (Jurnal Geomine, 2021)
The Coffee Plantation area is one of the main routes that can connect most of the districts in Central Sulawesi. This area has a height ranging from 25 masl to 900 masl above sea level, it is known that this area is above the Palu Metamorphic Rock Complex which is estimated to have a Pre-Tertiary age. This road section often experiences landslides due to high rainfall and the constituent materials on each slope. One way to determine the level of slope vulnerability is obtained by analyzing the engineering properties of residual soil on a slope. One of the methods to determine the factor of safety and displacement on the slope is to use the Finite Element Method by modeling it using the Plaxis V. 6 program. From the results of the analysis using the finite element method, the safety factor with gravity load is 1.061 and if external force is applied, the safety factor will decrease to 1.032. From the calculation results also obtained a material displacement of 0.448 meters with a gravitational force and a material displacement of 0.5 meters with an external load. so that the slope is categorized as unsafe.